The “attack-defence” game - Vorobev, N. (Lithuanian Mathematical Journal, 1968)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:Н. Н. Воробьев. Игра «нападение — защита»N. Vorobjovas. „Puolimo—gynybos“ lošimas